(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to examine the impact of the external auditor’s compliance with auditing standards on reducing creative accounting practices. To achieve the objectives of the study, a questionnaire was designed and distributed to a sample consisting of (30) external auditors working in the Qassim region. The study found a statistically significant relationship between the external auditor’s compliance with general (personal) standards and the reduction of creative accounting practices. In contrast, the results did not show a statistically significant relationship between compliance with fieldwork standards and the reduction of such practices. In light of the findings, the study recommends enhancing external auditors’ compliance with general (personal) standards, due to their effective role in improving audit procedures and reducing creative accounting practices. This can be achieved by focusing on professional and ethical aspects, strengthening auditor independence, enhancing professional competence, and intensifying continuous training programs for auditors. The study also recommends reconsidering the mechanisms for applying fieldwork standards and developing them to ensure greater effectiveness in detecting creative accounting practices. This includes improving audit evidence collection procedures, expanding substantive testing, and applying analytical review procedures in a more accurate and in-depth manner. Furthermore, the study recommends establishing clearer regulatory guidelines to reduce the multiplicity of accounting alternatives and treatments, thereby limiting opportunities for creative accounting practices and enhancing the comparability and reliability of financial statements for users.